PENGARUH PERILAKU MASYARAKAT DAN KONDISI LINGKUNGAN TERHADAP PENYAKIT DEMAM BERDARAH DENGUE DI KABUPATEN PELALAWAN PROVINSI RIAU - Mesi Yurez; Thamrin Thamrin; Riki Apriyandi (Program Pascasarjana Universitas Riau, 2018)
This research aimed at analyzing the relationship among people’s behavior with dengue fever which is 3M plus, environment condition, the existence of mosquito’s larvae, social-economics factor, and the dominant factor toward dengue fever in Pelalawan. The research was quantitative with case control study approach. The population was total of dengue fever patient in the working area of Pelalawan Berseri community health center. With the total were 31 cases and 31 controls. The measuring tool was Questionnaire which already done for validity and reliability by the former researcher. Also the medical devices to measure humidity, temperature, light intensity. The data were analyzed by using statistical test of chi square and logistic regression. The result showed that 3M plus variable is affecting the dengue fever (p value=0,001), The environment which is affecting it was humidity (p value=0,000), temperature (p value=0,032), light intencity (p value=0,000), and the existence of mosquito’s larvae (p value=0,000). Based on the comparison of the population numbers and dengue fever, it showed that there is a tendency of the increasing of dengue fever on the growth people’s population. The social impact that happen because of dengue fever are the change of family role, psychology disruption, worry, the change of social role, even the death of family member. The economic factor was the direct charge of health service which reaching rp.5.000.000 not including the blood transfusion. While, the family should spend the money for buying things outside the medical cost, it is about Rp 500.000 up to Rp 1.000.000 for foods, transportation, and the others. Another factor was the indirectly charge, such as the decreasing of family income because productive workday missing, because of sick, or need to take care for the family. The most dominant factor with dengue fever was the mosquito’s larvae with OR 10,668. Based on the result of the research, it should be done with the fixing of house components, such as the ventilation and the windows. the The effort about environment health can be done by the counseling from health departments, supported by the community health centers, about the importance of 3M plus program. And also the activation of jumantik members in all of the community health centers.